Applying human factor analysis tools to a railway brake and wheel maintenance facility. Issue 1 (9th March 2015) - Singh, Sarbjeet; Kumar, Rupesh; Kumar, Uday
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to demonstrate three techniques to extract human factor information from specific railway maintenance tasks. It describes the techniques and shows how these tools can be applied to identify improvements in maintenance practices and workflow. Design/methodology/approach – Three case studies were conducted on single group of technicians (n=19) at a railway maintenance workshop in Luleå, Sweden. Case study I examined the posture of the technicians while they were changing the brake shoes of freight wagons; the study employed the Standard Nordic Questionnaire and a videotape using the Ovako Working Posture Analysis System (OWAS). Case study II looked at maintenance repair times required to change the wheel axle on freight wagons at the workshop. A video filming method suggested by the European Agency for Safety and Health at Work was used to measure actual maintenance time. Finally, case study III considered the technicians' (n=19) perception of work demands, their control over the work and their social support while performing maintenance tasks (brake shoe and wheel axle maintenance); to this end, the case study used a demand control support questionnaire. Findings – In the first case study, the Standard Nordic Questionnaire confirmed that technicians at this particular railway vehicle maintenance workshop suffer from back and shoulder pain. The Ovako Working Posture Analysis showed that 21 percent of the working time required to fit the brake wedge and cotter pin fits into two OWAS categories: category 3, where "change is required as soon as possible, " and category 4, where "change is required immediately". Problems stem from poor workplace layout, incorrect posture and inaccessibility of tools and components. In the second study, the video analysis indicated that the working time to change the wheel axle of a freight wagon is greatly affected by poor workplace layout. The third case study showed that the technicians have lower "psychological demands" (mean=13), "higher control over work" (mean=16) and "high social support" (mean=22). Practical implications – The objective of this study was to apply knowledge about human factors to the functional relationships between maintenance personnel, tasks and the working environment to improve safety. If the workplace layout, working posture, maintenance manuals and accessibility of tools are poorly planned, maintenance performance can be adversely affected. The results of this study should assist maintenance management to design new policies and guidelines for improving the work environment. Originality/value – Three case studies were conducted at a railway maintenance workshop in Luleå, Sweden, to collect data on how human factors affect various railway maintenance tasks.